Peran Gaya Kepemimpinan Dan Tanggung Jawab Terhadap Kinerja Karyawan Dengan Variabel Motivasi Kerja Sebagai Mediasi Di KUD Setia Manggung - Galih Haikal Khadafi; Recky_ Recky (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
Employee performance plays a crucial role in determining organizational effectiveness, particularly in organizations that rely on service quality and employee commitment. Leadership style and work responsibility are considered important factors that influence employee performance, both directly and indirectly through psychological aspects such as work motivation. This study aims to analyze the effect of leadership style and responsibility on employee performance, with work motivation as a mediating variable at Koperasi Unit Desa (KUD) Setia Manggung.  This research employed a quantitative approach with an explanatory research design. The population consisted of all 38 employees of KUD Setia Manggung, and a saturated sampling technique was applied. Data were collected using a structured questionnaire and analyzed using Structural Equation Modeling based on Partial Least Square (SEM-PLS) with the assistance of SmartPLS 3 software. The results indicate that leadership style and responsibility have a positive and significant effect on employee performance. Both variables also significantly influence work motivation, while work motivation has a significant effect on employee performance. Furthermore, work motivation partially mediates the relationship between leadership style and employee performance, as well as between responsibility and employee performance. These findings highlight the importance of effective leadership, employee responsibility, and motivation in improving employee performance.